2012
DOI: 10.3892/mmr.2012.745
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis and biological behavior in pancreatic carcinoma and other pancreatic tumors

Abstract: Lymphatic vessels in primary tumor tissue play an important role in lymphatic metastasis. Lymphatic metastasis of malignant neoplasms is significantly related to prognosis, influencing both recurrence and survival. The aim of this study was to investigate the correlation of intra-tumoral lymphatic vessel density (iLVD) and peri-tumoral lymphatic vessel density (pLVD) with biological behavior and prognostic parameters in pancreatic carcinoma (PC) and other pancreatic tumors. Lymphangiogenesis was examined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Furthermore, the formation of new lymph vessels is an early process that develops before tumorigenesis, and as the tumor grows, the lymph vessels are inhibited or disabled. Our study also reports the same prognostic importance of LVD that was found by Wang et al [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the formation of new lymph vessels is an early process that develops before tumorigenesis, and as the tumor grows, the lymph vessels are inhibited or disabled. Our study also reports the same prognostic importance of LVD that was found by Wang et al [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, some studies suggest that intratumoral lymphatic vessel density (LVD) is not associated with lymphatic invasion or metastasis [11, 54]. Moreover, LVD is heterogeneous and PDACs can have collapsed lymphatic vessels which may interfere with cancer cell infiltration of lymph nodes [15, 54]. Nevertheless, some patients develop lymphatic metastases in the absence of robust lymphangiogenesis [11].…”
Section: Discussionmentioning
confidence: 99%
“…They also showed increased LVD within metastatic lymph nodes [154]. Wang, et al , found that increased peritumoral LVD in human pancreatic carcinoma tissues correlated with unfavorable tumor differentiation status, increased LVI, and more lymph node metastasis, while this was not the case for intratumoral LVD [53]. These data highlight the importance of peripancreatic lymphatics in the progression and metastasis of pancreatic cancer and their potential utility as both a predictor of patient outcomes and a possible therapeutic target.…”
Section: Lymphangiogenesismentioning
confidence: 99%
“…However, the prognostic value of mode of lymph node invasion is arguable: some studies report poorer overall survival in patients with lymphatic vessel-directed metastasis as compared to direct invasion [178], while other reports show no survival difference between the two modes of lymph node invasion [109,177]. Although lymph node invasion by PDAC occurs most frequently through the lymphatic vasculature, the LVD at the tumor site has not been conclusively correlated with either lymph node metastasis or prognosis due to conflicting study results [53,156,162,179]. This is also true for studies examining the expression of pro-lymphangiogenic factors such as VEGF-C and -D [162,180,181] (and in pancreatic endocrine tumors [182]).…”
Section: Pdac Invasion Of Lymphatic Vessels and Metastasis To The Lymmentioning
confidence: 99%